2020
DOI: 10.15537/smj.2020.2.24901
|View full text |Cite
|
Sign up to set email alerts
|

Functional somatic illnesses in patients with functional bowel disorders

Abstract: Objectives: To study the prevalence of functional gastrointestinal disorders (FGID) in Saudi patients with irritable bowel syndrome (IBS). Methods: A cross-sectional study was conducted in patients with IBS treated at a private tertiary medical center in western Saudi Arabia between 2013 and 2017. We used ROME 3 criteria with data from the Generalized Anxiety Disorder 7-item (GAD-7) scale, the Patient Health Questionnaire-9 (PHQ-9) depression scale, and International Classification of Headache Disorders (ICHD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…IBS symptoms can be triggered by several risk factors, including chronic stress [ 8 ], anxiety, depression [ 9 ], and smoking [ 10 ]. A cross-sectional study conducted in a tertiary medical center in Jeddah discovered a strong correlation with fibromyalgia, headache, and migraines [ 11 ]. According to the Rome IV criteria, a recent study conducted in Jazan found that the overall prevalence of IBS among the Jazan general population in Saudi Arabia was 16%.…”
Section: Introductionmentioning
confidence: 99%
“…IBS symptoms can be triggered by several risk factors, including chronic stress [ 8 ], anxiety, depression [ 9 ], and smoking [ 10 ]. A cross-sectional study conducted in a tertiary medical center in Jeddah discovered a strong correlation with fibromyalgia, headache, and migraines [ 11 ]. According to the Rome IV criteria, a recent study conducted in Jazan found that the overall prevalence of IBS among the Jazan general population in Saudi Arabia was 16%.…”
Section: Introductionmentioning
confidence: 99%